Lived Experience of Visual Impaired Children on Learning Opportunities and Challenges in Mainstream Classroom Settings (Spandan, 2023)
Education is a fundamental right of every child, and inclusive education focuses on accommodating students with special needs, including those who are visually impaired, by integrating them into mainstream classrooms. This paper explores how visually impaired children learn and interact with their sighted peers in an inclusive classroom setting. The study employs a phenomenological approach with a qualitative design to gather narratives about the learning experiences of visually impaired children. Interviews were conducted with purposefully selected bachelor-level students and teachers. The study revealed that peer support for visually impaired children was lower than anticipated. Additionally, teachers were perceived as not providing sufficient attention and care to these students. Despite this, visually impaired students expressed satisfaction with the opportunities afforded to them in this less-managed inclusive environment, as it offered them a better educational experience compared to traditional settings.